2021
DOI: 10.1186/s12890-021-01794-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypersensitivity pneumonitis is associated with an increased risk of venous thromboembolism: a retrospective cohort study

Abstract: Background Idiopathic pulmonary fibrosis (IPF) and chronic hypersensitivity pneumonitis share commonalities in pathogenesis shifting haemostasis balance towards the procoagulant and antifibrinolytic activity. Several studies have suggested an increased risk of venous thromboembolism in IPF. The association between venous thromboembolism and chronic hypersensitivity pneumonitis has not been studied yet. Methods A retrospective cohort study of IPF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…According to the literature, HP with fibrosis is accompanied by a significant risk of venous thrombosis and pulmonary embolism [15]. The presented patient's clinical presentation supported the diagnosis of pulmonary embolism, the origin of which was most likely venous thrombosis of the lower extremities.…”
Section: Discussionsupporting
confidence: 58%
“…According to the literature, HP with fibrosis is accompanied by a significant risk of venous thrombosis and pulmonary embolism [15]. The presented patient's clinical presentation supported the diagnosis of pulmonary embolism, the origin of which was most likely venous thrombosis of the lower extremities.…”
Section: Discussionsupporting
confidence: 58%
“…In ARDS, decreased fibrinolysis and increased coagulation activity can lead to a procoagulant state (11). Hypersensitivity pneumonitis may predispose patients to thromboembolism, possibly via inflammation and allergy-triggered activation of the coagulation cascade (12,13). In the present case, severe ARDS and suspicious hypersensitivity pneumonitis might have contributed to uncontrollable thrombosis at the transfer to our hospital.…”
Section: Pediatric Emergency Medicine Journalmentioning
confidence: 64%
“…Meanwhile, higher incidence of VTE in IPF was also observed of 3.5%. A retrospective study by Sobiecka M et al [31] on 441 patients with ILD showed that HP and IPF had similar VTE incidence rates of 3.3% and 4.6%, respectively. We further demonstrated similar VTE incidence between these two ILD types (HP, 3.6%; IPF, 3.5%).…”
Section: Discussionmentioning
confidence: 99%